PANCASILA AS THE FOUNDATION FOR THE IMPLEMENTATION OF NATIONAL SECURITY: ADDRESSING NON-MILITARY THREATS IN INDONESIA - Mullah, Ilham Fakih; Prihartoro, Mitro; Arbiansyah, Tri Panca Titis; Setiawibawa, Rachmat (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Indonesia's national security can be implemented primarily through defense, focusing on territorial, sovereign, and social dimensions. Threats to national security are categorized into military and non-military threats. Non-military threats have become increasingly significant in Indonesia, as the public expresses greater concern about issues affecting their well-being, such as social injustice, intolerance, and health crises. Therefore, a national security strategy must prioritize a holistic and integrated approach grounded in Pancasila as the nation's legal and moral foundation. Pancasila functions not only as the state ideology but also as a moral and legal basis for formulating responsive defense and security policies aimed at preserving national unity and stability. This study explores the relationship between the application of Pancasila values and national security, particularly in addressing non-military threats. Employing a qualitative approach and literature review, the research concludes that Pancasila plays a vital role in shaping adaptive and integrative policies to confront future national security challenges. It also emphasizes the importance of inter-agency collaboration and active community participation in strengthening national resilience.